Low-Operating-Temperature NO2 Sensor Based on a CeO2/ZnO Heterojunction - Kai Sun; Guanghui Zhan; Hande Chen; Shiwei Lin (Sensors, 2021)
CeO2/ZnO-heterojunction-nanorod-array-based chemiresistive sensors were studied for their low-operating-temperature and gas-detecting characteristics. Arrays of CeO2/ZnO heterojunction nanorods were synthesized using anodic electrodeposition coating followed by hydrothermal treatment. The sensor based on this CeO2/ZnO heterojunction demonstrated a much higher sensitivity to NO2 at a low operating temperature (120 °C) than the pure-ZnO-based sensor. Moreover, even at room temperature (RT, 25 °C) the CeO2/ZnO-heterojunction-based sensor responds linearly and rapidly to NO2. This sensor’s reaction to interfering gases was substantially less than that of NO2, suggesting exceptional selectivity. Experimental results revealed that the enhanced gas-sensing performance at the low operating temperature of the CeO2/ZnO heterojunction due to the built-in field formed after the construction of heterojunctions provides additional carriers for ZnO. Thanks to more carriers in the ZnO conduction band, more oxygen and target gases can be adsorbed. This explains the enhanced gas sensitivity of the CeO2/ZnO heterojunction at low operating temperatures.